Selective cyclin-dependent kinase 4/6 inhibitors as anticancer drugs: Moving beyond hormone receptor-positive breast cancer - Tamojit Chaudhuri; K Govind Babu; K C Lakshmaiah; Lokanatha Dasappa; Linu Abraham Jacob; M C Suresh Babu; A H Rudresha; K N Lokesh; L K Rajeev (Indian Journal of Medical and Paediatric Oncology)
The cyclin D-cyclin-dependent kinase (CDK) 4/6 pathway controls the cell cycle machinery by regulating the G1-to-S-phase transition. Dysregulation of this pathway, resulting in increased cellular proliferation, is frequently observed in a variety of human cancers. Activation of cyclin D-CDK 4/6 pathway can occur through different mechanisms, including gene amplification/rearrangement, loss of negative regulatory factors, epigenetic modifications, and point mutations of different components of this pathway. Quite conspicuously, CDK 4/6 inhibitors have emerged as promising anticancer agents in various tumors in which CDK 4/6 has a pivotal role in the G1-to-S-phase cell cycle transition. The clinical use of first-generation, nonselective pan-CDK inhibitors was not progressed beyond early phase trials, due to unacceptable toxicity and lack of efficacy noted with these agents. The emergence of selective CDK 4/6 inhibitors, including ribociclib, abemaciclib, and palbociclib, has enabled us to effectively target cyclin D-CDK 4/6 pathway, at the cost of acceptable toxicity. The results of landmark Phase III trials investigating palbociclib and ribociclib in advanced hormone receptor (HR)-positive breast cancer have demonstrated a substantial clinical benefit with a well-tolerated toxicity profile. Mechanisms of acquired resistance to selective CDK 4/6 inhibitors are beginning to emerge. Clearly, a detailed understanding of these resistance mechanisms is very much essential for the rational development of post-CDK 4/6 inhibitor therapeutic strategies. Extending the use of selective CDK 4/6 inhibitors beyond HR-positive breast cancer is a challenging task and will likely require identification of clinically meaningful biomarkers to predict response and the use of combination approaches to optimize CDK 4/6 targeting.